The Far‐UV Albedo of Europa From HST Observations. Issue 5 (31st May 2018) - Becker, T. M.; Retherford, K. D.; Roth, L.; Hendrix, A. R.; McGrath, M. A.; Saur, J.
Abstract: We present an analysis of Europa's far‐UV spectral albedo using observations during the 1999–2015 time period made by the Space Telescope Imaging Spectrograph on the Hubble Space Telescope. Disk‐integrated observations show that the far‐UV spectrum in the ~130 to 170‐nm range is relatively flat or slightly blue (increasing albedo with decreasing wavelength) for the studied hemispheres: the leading, trailing, and anti‐Jovian hemispheres. At Lyman‐α (121.6 nm), the albedo of the trailing hemisphere continues the blue trend, but it reddens for the leading hemisphere. Also at this wavelength, the albedo of the leading hemisphere, which is higher than the trailing hemisphere at near‐UV and visible wavelengths, is lower than the trailing hemisphere, exhibiting spectral inversion. We find no evidence of a sharp water‐ice absorption edge at 165 nm on any hemisphere of Europa, which is intriguing since such an absorption feature has been observed on the icy Saturnian satellites. Plain Language Summary: We used observations spanning from 1999 to 2015 obtained by the Space Telescope Imaging Spectrograph on the Hubble Space Telescope to study the surface reflectance of Europa at far‐ultraviolet (UV) wavelengths. We find that Europa has a low reflectance in the UV and that there is little variation in the surface brightness at most of the UV wavelengths. When observed at visible wavelengths, one of Europa's hemispheres is brighter than the other, but at the UV wavelength of 121.6 nm, the hemisphere brightness is reversed. We also find that Europa looks different from the icy moons of Saturn at far‐UV wavelengths. Key Points: HST observations show that the spectrum of Europa in the far‐UV is very flat or slightly blue At Lyman‐alpha, Europa is brighter on the leading hemisphere than the trailing, opposite of what is observed in the visible and near‐UV Europa's spectrum lacks the sharp absorption feature at 165 nm observed on the icy Saturnian satellites